Monkeys - Courtauld, Sarah Lucy.; Howarth, Daniel (Tulsa, Okla. : EDC Pub., 2009)
An illustrated introduction to monkeys with simple text that describes unique physical characteristics, habitats, behavior, diet, and other topics.
Includes index.
2.6
K-3
Keywords: Monkeys; Readers (Elementary).